A STUDY SEPARATION OF STARCH AND MALTOSE USING CELLULOSE ACETATE â SILICA FUME MEMBRANES - Emmalina P, Astried
The focus of this research is the separation of a mixture of maltose and starch using cellulose acetate (CA) - silica fume (SF). Significant differences in size between starch and maltose is the reason of using a membrane in this separation. In this experiment, membranes were made by phase inversion technique towards a mixture of cellulose acetate and silica fume, with the composition of cellulose acetate in a range of while 9 - 18%, the ratio of CA and SF were varied. The performance of such membranes in separation processes could be generally expressed as membrane permeability and selectivity. Membrane permeability and selectivity data were obtained from filtration experiment demineralized water and a mixture of starch - maltose solution. Such membrane could separate the mixture of starch and maltose with a rejection toward starch in a range of 11 – 95% and rejection towards maltose in a range of 0 – 86%. All fabricated membranes were tested in a filtration cell under operational pressure varied from 1 to 3 bars (depending on mechanical strength of the membrane). The membrane consist of 18% cellulose acetate and has a ratio of CA-SF = 6:1 gives a 95.27% rejection towards starch and a 86.21% rejection towards maltose. This membrane has thickness 0.235 mm in average. Rejection of CA-SF membrane towards starch and maltose will proportionally increase a long with the increase of polymer concentration in the membrane. Morphologycal analysis of the membrane was observed by SEM.